Suppression of Ionospheric Irregularity Due to Auroral Particle Impact. Issue 1 (29th December 2021) - Takahashi, Toru; Spicher, Andres; Di Mare, Francesca; Rowland, Douglas E.; Pfaff, Robert F.; Collier, Michael R.; Clausen, Lasse Boy Novock; Moen, Jøran Idar
Abstract: The VISIONS‐2 35.039 sounding rocket was launched from Ny‐Ålesund, Svalbard, on 7 December 2018 at 11:06 UT, and traveled overhead of the cusp aurora. The payload reached an apogee of 806.6 km and provided measurements of the electric field ( E ) and electron density ( N e ) with a high sampling rate of 6, 250 Hz. The high‐sampling‐data make it possible to estimate the horizontal structure of E and N e on scales ranging from meters to kilometers scale. The horizontal variation in the electron density and electric field (Δ N e / N e and Δ E ) and integrated power of N e and E (Σ P Ne and Σ P E ) for 1–10, 10–100, and 100–1, 000 Hz range were derived. The derived values were compared with the 557.7 and 630.0 nm emission intensities obtained from an all‐sky camera installed in Ny‐Ålesund projected at the footprint of the rocket, which was calculated by tracing the Earth's magnetic field line from the rocket altitude to the emission layer. Δ N e / N e, Δ E, Σ P Ne, and Σ P E increased with the 630.0 nm emission intensity. Of particular interest is the lower level irregularity was observed when the 557.7 nm emission intensity exceeded 4.5 kR compared with other time interval. This may suggest that particle impact ionization created sufficient Pedersen conductance in the E ‐region to short the F ‐region current. This short‐circuit seemed to cause the suppression of the irregularities in the F ‐region and lower level irregularities were also observed in the rocket altitude. Key Points: The ionospheric irregularities and cusp auroral emission were observed by rocket in‐situ and ground based measurement simultaneously The increased level of plasma irregularities observed in‐situ is associated with the ground‐based 630 nm emission The auroral particle impacts in the E ‐region are a possible driver of the suppression of F ‐region irregularity